Kajian Sosiologi Sastra Terhadap Unsur Moral pada Kumpulan Puisi Doa untuk Anak Cucu Karya W. S. Rendra sebagai Alternatif Bahan Ajar Sastra di Kelas X SMA - Irsyad Muhammad Ridhwan; Panca Pertiwi Hidayati; Desti Fatin Fauziyyah (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This study aims to examine the moral elements in the poetry collection Doa Untuk Anak Cucu by W. S. Rendra. The results of the study, for alternative teaching materials for students at the Senior High School level class X. Students often find difficulties when analyzing the moral elements contained in poetry, one of the factors is the difficulty of finding the right teaching materials and only using teaching materials that are already available, there is no development of innovative teaching materials. This research uses descriptive qualitative method. The data source of this research is the book collection of poems Doa Untuk Anak Cucu by W. S. Rendra. The results of the analysis of moral elements in the poetry collection Doa Untuk Anak Cucu by W. S. Rendra, are as follows: Four moral elements were found, including man's relationship with himself, man's relationship with nature, man's relationship with society, and man's relationship with his God. The results of the data that have been studied fulfill the general characteristics of the study of the moral elements in poetry. Thus, the literary sociology analysis of the moral elements in the poetry collection Doa Untuk Anak Cucu by W. S. Rendra as an alternative literature teaching material in class X Senior High School, shows success.